Ready to eat, ready to wear - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
One day, you could eat your hat - and more! An American company is currently developing a new line of textile fibres, based on maize starch, which can be used just like petroleum-based synthetic fibres. Cargill Dow Polymers is preparing to launch a...